Toxocariasis in Cuba: a literature review. - Idalia Sariego; Kirezi Kanobana; Lázara Rojas; Niko Speybroeck; Katja Polman; Fidel A Núñez (Public Library of Science (PLoS), 2012)
Human toxocariasis (HT) is a zoonotic disease caused by infection with the larval stage of Toxocara canis, the intestinal roundworm of dogs. Infection can be associated with a wide clinical spectrum varying from asymptomatic to severe organ injury. While the incidence of symptomatic human toxocariasis appears to be low, infection of the human population is widespread. In Cuba, a clear overview on the status of the disease is lacking. Here, we review the available information on toxocariasis in Cuba as a first step to estimate the importance of the disease in the country. Findings are discussed and put in a broader perspective. Data gaps are identified and suggestions on how to address these are presented. The available country data suggest that Toxocara infection of the definitive dog host and environmental contamination with Toxocara spp. eggs is substantial, but information on HT is less conclusive. The availability of adequate diagnostic tools in the country should be guaranteed. Dedicated studies are needed for a reliable assessment of the impact of toxocariasis in Cuba and the design of prevention or control strategies.